Euthanasia in South Africa: Philosophical and theological considerations - Mojalefa L.J. Koenane (Verbum et Ecclesia, 2017)
Debates on euthanasia (or mercy killing) have been a concern in moral, philosophical, legal, theological, cultural and sociological discourse for centuries. The topic of euthanasia inspires a variety of strong views of which the slippery slope argument is one. The latter warns that the principle(s) underlying any ethical issue (including euthanasia) may be distorted. Scholars views on euthanasia are influenced mainly by cultural, personal, political and religious convictions. In South Africa, the issue of euthanasia has arisen from time to time, but the question of whether it should be legalised was not seriously considered until it recently attracted attention because of a particular case, that of Cape Town advocate Robin StranshamFord. Although euthanasia is still illegal (this is because the Stransham-Ford ruling is confined to this particular case only), as stated in the ratio decidendi by Judge Hans Fabricius of the High Court in Pretoria, the Court granted leave to appeal its April 2015 judgement regarding euthanasia in the application lodged by Stransham-Ford. In considering the contentious nature of the issue of euthanasia, this article adopts a multidisciplinary approach which includes historical, legal, theological, philosophical, theoretical and analytic frameworks, discussing euthanasia from philosophical and theological perspectives, in particular. We conclude by recommending that the subject of applied ethics, which helps to educate citizens about contemporary moral problems such as euthanasia, be introduced at school level. Exposing young people to the debates around thorny issues such as this would familiarise them with the discourse, encourage them to engage with it and empower them as mature citizens to make informed, reasonable decisions, obviating confusion and conflict which might otherwise arise. The problems surrounding the issue of euthanasia are multidimensional and have the capacity to polarise the nation and destroy families. Intradisciplinary and/or interdisciplinary implications: The article challenges government tendencies to decide on its own to make policy decisions on which society does not have input; thus against the Batho Pele principle of participation. We suggest that applied ethics be introduced earlier at the school level and be carried onto tertiary education to ensure effective citizen participation.